Analysis of Teacher Competence in Islamic Perspective and Regulation of the Minister of National Education - Fajriah, Ulya; Wachidah, Nor; Ningrum, Ayu Reza; Febriani, Evi; Saputra, Devid (International Journal of Education, Information Technology, and Others, 2025)
This research discusses the analysis of teacher competency from an Islamic perspective and the Minister of National Education Regulation. Teachers have a central role in education. Teacher competency is very important to achieve national education goals. Teacher competency covers many aspects, including knowledge, skills and behavior that teachers must possess, internalize and master in carrying out their professional duties. This research highlights that the low level of teacher professionalism is due to a lack of teacher competence. The method used in this research is the library method, namely a research method whose data sources come from books, scientific articles, journals, or other research results related to the problem topic. Thus, this research aims to determine teacher competency which causes low teacher professionalism